Thermosensitive Shape-Memory Poly(stearyl acrylate-co-methoxy poly(ethylene glycol) acrylate) Hydrogels - Hideaki Tokuyama; Ryo Iriki; Makino Kubota (Gels, 2023)
Stimuli-sensitive hydrogels are highly desirable candidates for application in intelligent biomaterials. Thus, a novel thermosensitive hydrogel with shape-memory function was developed. Hydrophobic stearyl acrylate (SA), hydrophilic methoxy poly(ethylene glycol) acrylate (MPGA), and a crosslinking monomer were copolymerized to prepare poly(SA-co-MPGA) gels with various mole fractions of SA (xSA) in ethanol. Subsequently, the prepared gels were washed, dried, and re-swelled in water at 50 °C. Differential scanning calorimetric (DSC) and compression tests at different temperatures revealed that poly(SA-co-MPGA) hydrogels with xSA > 0.5 induce a crystalline-to-amorphous transition, which is a hard-to-soft transition at ~40 °C that is based on the formation/non-formation of a crystalline structure containing stearyl side chains. The hydrogels stored in water maintained an almost constant volume, independent of the temperature. The poly(SA-co-MPGA) hydrogel was soft, flexible, and deformed at 50 °C. However, the hydrogel stiffened when cooled to room temperature, and the deformation was reversible. The shape-memory function of poly(SA-co-MPGA) hydrogels is proposed for potential use in biomaterials; this is partially attributed to the use of MPGA, which consists of relatively biocompatible poly(ethylene glycol).